Implementasi Sistem Pencatatan dan Pedigree sebagai Upaya Optimalisasi Produksi Ternak Kambing Lokal - Rahma Jan; Lalu Muhammad Kasip; Maskur; Tapaul Rozi; Muhammad Muhsinin (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service program aims to improve the productivity and management of goat farming in Central Lombok through the implementation of a livestock data recording system, understanding of pedigree, and health monitoring technology. The main issues faced by the partners include the lack of a structured recording system, limited knowledge of pedigree-based breeding, weak reproductive management, and low access to livestock product marketing. Therefore, this program focuses on empowering farmers through socialization, training, mentoring, and the formation of independent farmer groups for the sustainability of the program. The implementation results show significant achievements. As many as 80% of farmers were able to apply the livestock recording system either manually or digitally, with 90% data accuracy. Pedigree training enhanced the farmers' understanding of breeding, with 90% of farmers mastering the concept, and 75% of livestock from selective breeding showed superior quality. The use of health monitoring applications by 80% of farmers was able to reduce livestock mortality by 20% within six months. Additionally, the implementation of the recording system increased the birth ratio by 25%. The sustainability of the program is maintained with the formation of independent farmer groups that serve as platforms for information sharing and supporting the consistency of technology application. 75% of farmers continued recording practices, pedigree-based breeding, and health monitoring after the program ended. Factors supporting sustainability include the capacity of farmers and support from extension workers, higher education institutions, and local governments. Overall, the program successfully improved efficiency, genetic quality of livestock, reduced mortality, and strengthened farmers' independence, and it has the potential to be replicated in other regions.